Tracking illegal activities using video surveillance systems: a review of the current state of research - D. O. Zhadan; M. V. Mordvyntsev; D. V. Pashniev (Law and Safety)
The current state of research on the use of the neural networks under martial law to identify offenders committing illegal acts, prevent acts of terrorism, combat sabotage groups in cities, track weapons and control traffic is considered. The methods of detecting illegal actions, weapons, face recognition and traffic violations using video surveillance cameras are analysed. It is proposed to introduce the studied methods into the work of “smart” video surveillance systems in Ukrainian settlements.